Sex-specific differences in primary Sjögren's disease - Punnanitinont, Achamaporn; Kramer, Jill M. (Frontiers in Dental Medicine, 2023)
Many autoimmune diseases show a striking female sex predilection, including primary Sjögren's disease (pSD). Patients with pSD display exocrine gland pathology, such as salivary hypofunction and salivary and lacrimal gland inflammation. Moreover, many serious systemic disease manifestations are well-documented, including interstitial nephritis, hypergammaglobulinemia and neuropathies. Of note, women and men with pSD display distinct clinical phenotypes. While the underlying reasons for these clinical observations were poorly understood for many years, recent studies provide mechanistic insights into the specific regulatory landscapes that mediate female susceptibility to autoimmunity. We will review factors that contribute to the female sex bias, with an emphasis on those that are most relevant to pSD pathogenesis. Specifically, we will focus on sex hormones in disease, genetic alterations that likely contribute to the significant disease prevalence in females, and studies that provide evidence for the role of the gut microbiota in disease. Lastly, we will discuss therapeutics that are in clinical trials for pSD that may be particularly efficacious in targeting signaling networks that mediate inflammation in a sex-specific manner.